Higher Education in Asia/Pacific - Bigalke, Terance W. author. aut Link
XIX, 268 p.
Keywords: Expansion and privatization have created new concerns over the quality of education throughout the Asia/Pacific region. This volume provides a framework to examine these challenges in the region and beyond.